Expressive Brand Relationship, Brand Love, and Brand Loyalty for Tablet PCs: Building a Sustainable Brand - Zhang, Shikun; Peng, Michael Yao-Ping; Peng, Yaoping; Zhang, Yuan; Ren, Guoying; Chen, Chun-Chun (Frontiers in Psychology, 2020)
This study was conducted from the strategic marketing perspective to test the impact of brand relationship types on brand loyalty. We also test three path effects of brand love and brand trust. Data were collected from three metropolitan customers who use tablet PCs. We obtained 383 valid samples, giving a valid response rate of 89%. Data analysis was performed with SmartPLS2.0 and SPSS 23.0 to test the proposed model. The results indicate that an expressive brand relationship significantly predicts brand trust and brand loyalty. In turn, brand trust has a positive influence on brand love, while brand awareness and brand love influence attitudinal and behavioral loyalty. Expressive brand relationship has two indirect mediating affects via brand trust and brand love, which influence brand loyalty. Finally, we suggest managerial implications and directions for future research.